Advances in Computation and Intelligence 5th International Symposium, ISICA 2010, Wuhan, China, October 22-24, 2010. Proceedings - Cai, Zhihua; Hu, Chengyu; Kang, Zhuo.; Liu, Yong.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Volumes CCIS 107 and LNCS 6382 constitute the proceedings of the 5th International Symposium, ISICA 2010, held in Wuhan, China, in October 2010. ISICA 2010 attracted 267 submissions and through rigorous reviews 53 papers were included in LNCS 6382. The papers are presented in sections on ANT colony and particle swarm optimization, differential evolution, distributed computing, genetic algorithms, multi-agent systems, multi-objective and dynamic optimization, robot intelligence, statistic learning and system design.
Section I: Ant Colony and Particle Swarm Optimization -- A Discrete PSO-Based Fault-Tolerant Topology Control Scheme in Wireless Sensor Networks -- Retracted: Feature Selection Using Ant Colony Optimization for Text-Independent Speaker Verification System -- GPS Height Fitting Using Gene Expression Programming -- Parameter Evolution for a Particle Swarm Optimization Algorithm -- The Ant Colony Optimization Algorithm for Multiobjective Optimization Non-compensation Model Problem Staff Selection -- Section II: Differential Evolution -- A New Self-adaption Differential Evolution Algorithm Based Component Model -- A Novel Interpolation Method Based on Differential Evolution-Simplex Algorithm Optimized Parameters for Support Vector Regression -- A Variant of Differential Evolution Based on Permutation Regulation Mechanism -- Differential Evolution Based Band Selection in Hyperspectral Data Classification -- Diversity Analysis of Opposition-Based Differential Evolution$1 (BAn Experimental Study -- Hybrid Differential Evolution Algorithm with Chaos and Generalized Opposition-Based Learning -- Self-adapting Differential Evolution Algorithm with Chaos Random for Global Numerical Optimization -- Section III: Distributed Computing -- A Concurrent-Hybrid Evolutionary Algorithms with Multi-child Differential Evolution and Guotao Algorithm Based on Cultural Algorithm Framework -- A Hierarchical Distributed Evolutionary Algorithm to TSP -- A New Distributed Node Localization Scheme Using a Mobile Beacon -- A Novel Multi-Population Genetic Algorithm for Multiple-Choice Multidimensional Knapsack Problems -- Comparative Analysis for k-Means Algorithms in Network Community Detection -- Framework for Distributed Evolutionary Algorithms in Computational Grids -- Section IV: Genetic Algorithms -- A Review of Tournament Selection in Genetic Programming -- Genetic Algorithm for Mixed Chinese Postman Problem -- Hybrid Evolutionary Algorithms Design Based on Their Advantages -- Hybridized Optimization Genetic Algorithm for QOS-Based Multicast Routing Problem -- Retroviral Iterative Genetic Algorithm for Real Parameter Function Optimization Problems -- The RM-MEDA Based on Elitist Strategy -- Section V: Multi-agent Systems -- A Proactive Perception Model in Agent-Based Software Integration and Evolution -- Algorithmic Trading Strategy Optimization Based on Mutual Information Entropy Based Clustering -- An Improved Similarity Algorithm Based on Hesitation Degree for User-Based Collaborative Filtering -- Intrusion Detection System Based on Support Vector Machine Active Learning and Data Fusion -- Long-Distant Pipeline Emergency Command Decision-Making System Based on Agent -- Sales Forecasting Based on ERP System through BP Neural Networks -- Section VI: Multi-objective and Dynamic Optimization -- Capacity Allocation Policy of Third Party Warehousing with Dynamic Optimization -- Dynamical Multi-objective Optimization Using Evolutionary Algorithm for Engineering -- Faster Convergence and Higher Hypervolume for Multi-objective Evolutionary Algorithms by Orthogonal and Uniform Design -- Multi-objective Fuzzy Clustering Method for Image Segmentation Based on Variable-Length Intelligent Optimization Algorithm -- Perspectives in Dynamic Optimization Evolutionary Algorithm -- Section VII: Robot Intelligence -- A Real Time Vision-Based Hand Gestures Recognition System -- A Virtual Robot Arm Model with Force Feedback and Contact States Identification -- Improving Reading Comprehension Using Knowledge Model -- Modular Robot Path Planning Using Genetic Algorithm Based on Gene Pool -- Pathfinder Based on Simulated Annealing for Solving Placement and Routing Problem -- Section VIII: Statistical Learning -- Application of Data Mining in Multi-Geological-Factor Analysis -- Applying an Artificial Neural Network to Building Reconstruction -- Fast Dimension Reduction Based on NMF -- Frequent Words$1 (BGrammar Information in Chinese Chunking -- Multilabel Classification Using Error Correction Codes -- Test-Cost Sensitive Classification Using Greedy Algorithm on Training Data -- Section IX: System Design -- 3-D Magnetotelluric Adaptive Finite-Element Modeling -- A Study on Modeling Evolutionary Antenna Based on ST-5 Antenna and NEC2 -- A Synthesis of Four-Branch Microwave Antenna by Evolution Algorithm and Orthogonal Experiment -- Band Structures of Multilayer Films with Randomness -- Fast Principal Component Analysis Based on Hardware Architecture of Generalized Hebbian Algorithm -- The Data-Based Mathematical Modeling and Parameter Identification in JAK-STAT Signaling Pathway by Using a Hybrid Evolutionary Algorithm -- The Research on the Intelligent Interpreter for ISO 14649 Programs -- Erratum -- Erratum: Feature Selection Using Ant Colony Optimization for Text-Independent Speaker Verification System.s
Keywords: Computer science; Computer software; Information systems; Artificial intelligence; Computer simulation; Bioinformatics; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Simulation and Modeling; Computational Biology/Bioinformatics.